1988
DOI: 10.1080/02626668809491247
|View full text |Cite
|
Sign up to set email alerts
|

Soil and water losses in a low intensity rainfall region in Iraq

Abstract: The rainfed region of northern Iraq experiences moderate to severe water erosion. The area is characterized by low intensity rainfall, so erosion characteristics in the region may differ from those of regions with high intensity rainfall. Data from two natural runoff plots in the region were used to derive preliminary rainfall-runoff and soil erosion relationships. Runoff was found to vary linearly with rainfall. Interrill or sheet erosion was the dominant erosion type on the plots. Soil loss varied exponentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Palestinian plot studies by Hammad et al (2006) showed that runoff and soil erosion were both likely to occur in rain events in which R t30 > 4 mm h 1 , quite a low rate. Low rain rate thresholds for overland flow and erosion have been reported elsewhere (Hussein and Othman, 1988;James and Alexander, 1998;Kumar et al, 2002). For erosion on burned hillslopes, Robichaud et al (2006) reported significant erosion for events in which R t10 exceeded 13 mm h 1 , and for which R e values (not reported) would have been considerably lower.…”
Section: The Environmental Impact Of Rain Events With Low Rain Ratessupporting
confidence: 54%
“…Palestinian plot studies by Hammad et al (2006) showed that runoff and soil erosion were both likely to occur in rain events in which R t30 > 4 mm h 1 , quite a low rate. Low rain rate thresholds for overland flow and erosion have been reported elsewhere (Hussein and Othman, 1988;James and Alexander, 1998;Kumar et al, 2002). For erosion on burned hillslopes, Robichaud et al (2006) reported significant erosion for events in which R t10 exceeded 13 mm h 1 , and for which R e values (not reported) would have been considerably lower.…”
Section: The Environmental Impact Of Rain Events With Low Rain Ratessupporting
confidence: 54%
“…In addition, the value of R 2 is relatively high (0.93) which means 93% variations in dependent variable Y are explained by the independent variables present in our model as shown in Figs. 3 and 4 (Abdulla & Al-badranih (2000), Najmaddin et al (2017), Hussein & Othman (1988)). Figure 5 illustrates the strong correlation between the two factors.…”
Section: Resultsmentioning
confidence: 99%
“…Common erosion/sedimentation analysis relates the runoff ratio to the sediment delivery ratio (ratio of sediment yield to gross erosion) (Hussein & Othman, 1988). Only the long plots, however, showed noticeable sediment enrichment in fines compared to the original soil (Hussein, 1996).…”
Section: P and N Lossmentioning
confidence: 99%